Analisis Semiotik Buku Cerita Bergambar "Gambar Lucu Mika": Pendidikan Literasi Digital - Nabella, Chykita Gebby (SAP (Susunan Artikel Pendidikan), 2024)
Introducing digital literacy to children is very important from an early age. Gadgets have features that trigger challenges as well as fun for children so that children need to receive digital literacy education from an early age to teach children to use gadgets wisely. This research aims to focus on picture books as one of the interesting educational media for early childhood. The book entitled Gambar Lucu Mika, which is a non-text model book published by Pusat Perbukuuan (Pusbuk), Kemendikbudristek, by Tyas Widjati, was deliberately chosen because it contains the basic concept of digital literacy education, namely teaching children to be wise in playing gadgets. Through a qualitative approach and semiotic analysis method of Ferdinan De Saussure's model, it was found that the combination of text and illustration image which is a signifier can contain a signified in the form of associative meaning of both. The meaning revealed is the difference in meaning that represents the feelings of each emoticon sent as a basic knowledge in digital literacy education. Conflict resolution without the help of parents in this storybook teaches children to be able to take responsibility and solve their own problems. Therefore, the picture storybook Gambar Lucu Mika can be used as a medium for digital literacy education from an early age so that children can be wiser in using gadgets.